Characterization of a conjunctival melanoma cell line CM-AS16, newly-established from a metastatic Han Chinese patient. (August 2018) - Li, Yongyun; Shang, Qingfeng; Li, Peng; Cao, Jinfeng; Zhu, Liqi; Jager, Martine J.; Fan, Xianqun; Ge, Shengfang; Jia, Renbing
Abstract: Conjunctival melanoma (CM) is associated with metastases formation, can be fatal, and occurs in all different races. While cell lines are essential for experimental research, all available CM cell lines are derived from Caucasian patients. Furthermore, they are not derived from metastases. We aimed to establish a new CM cell line from a parotid metastasis in a Han Chinese patient and to depict its characteristics. The novel cell line, CM-AS16, was obtained from a surgical parotid sample and determined as a unique one with short tandem repeat (STR) analysis. It has been successively sub-cultured in vitro for more than 100 passages and exhibits rapid proliferation and migration. Chromosome analysis shows abundant chromosome aberrations, while whole exome sequencing (WES) reveals a typical NRAS mutation (Q61R). In vivo tumor growth was successfully established in a NOD/SCID mice model, and the immunophenotypes, such as HMB45, Melan A, S100, SOX10 and Ki67, manifested similar between the original tumor and the xenograft by immunohistochemistry. A MEK inhibitor binimetinib prominently suppressed in vitro cell growth by inhibiting ERK1/2 phosphorylation. In addition, monoclonal cells were used to demonstrate the drug sensitivity of different cells. In conclusion, the first cell line, CM-AS16, that is derived from a CM in a Han Chinese patient has highly malignant characteristics and a typical NRAS mutation. It may be used as a tool for further exploration of the molecular mechanisms of CM. Highlights: Successful established CM-AS16, a novel metastatic CM cell line from a Han Chinese patient. Malignant characteristics and a typical NRAS mutation was confirmed. Binimetinib prominently suppressed cell growth by inhibiting ERK1/2 phosphorylation. CM-AS16 could be used as a tool for further research in CM, especially the metastatic mechanism.